Local feminist perspectives as transformation levers for sustainable development in Ukraine in the context of ongoing defence - Olena Oleksandrivna Strelnyk; Liudmyla Yuzva; Tamara Zlobina (German Institute of Development and Sustainability (IDOS), 2025)
The research in this discussion paper explores the significant role of feminist perspectives and actions in fostering sustainable gender-transformative changes within Ukraine, particularly during the ongoing defence against Russian aggression. It highlights the ability of feminist movements to catalyse long-term shifts towards gender equality and social inclusion, with a focus on women's and LGBT+ rights. Despite the challenges of war, feminist activists continue to push for transformative policies that not only address immediate wartime needs, but also lay the foundation for gender-responsive defence, inclusive recovery and post-war reconstruction. This study examines the impact of feminist actions and perspectives on various sectors of Ukrainian society, the barriers they face and the opportunities that remain for strengthening feminist policies during and after the war. The research timeline spans 2014-2024, corresponding to the duration of Russia's war against Ukraine, with a particular emphasis on the period of the full-scale invasion from 2022 to 2024.
Keywords: 320; Gender; Ukraine; Feminism